2019
DOI: 10.1055/s-0039-1692473
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictive Factors for Additional Opioid Prescription after Endoscopic Skull Base Surgery

Abstract: Introduction Postoperative pain management and opioid use following endoscopic skull base surgery (ESBS) is not well understood. A subset of patients requires additional opioid prescription (AOP) in the postoperative period. The objective of this study is to describe the incidence of AOP, as well as evaluate patient and surgical characteristics that may predict additional pain management requirements following ESBS. Methods A retrospective review of cases undergoing ESBS between November 2016 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…However, few studies to date have a sample size large enough to study opioid prescribing patterns specifically in patients undergoing skull base surgery for VS. Boyd et al conducted a prospective observational study in patients undergoing otologic and neurotologic surgeries over a 6-month period and found that the majority of pain pills went unused (20); however, only eight patients in the study underwent lateral skull base surgery and the specific procedures were not specified. A recent series of 42 patients undergoing endoscopic anterior skull base surgery found 21.4% required additional prescription, and patient-level factors such as younger age, comorbid depression, and preoperative opioid use increased the odds of requiring additional opioids postoperatively (21). Nonetheless, despite the growing interest in improving the quality of life of patients with VS undergoing surgery, few recent studies have focused on their postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have a sample size large enough to study opioid prescribing patterns specifically in patients undergoing skull base surgery for VS. Boyd et al conducted a prospective observational study in patients undergoing otologic and neurotologic surgeries over a 6-month period and found that the majority of pain pills went unused (20); however, only eight patients in the study underwent lateral skull base surgery and the specific procedures were not specified. A recent series of 42 patients undergoing endoscopic anterior skull base surgery found 21.4% required additional prescription, and patient-level factors such as younger age, comorbid depression, and preoperative opioid use increased the odds of requiring additional opioids postoperatively (21). Nonetheless, despite the growing interest in improving the quality of life of patients with VS undergoing surgery, few recent studies have focused on their postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by Rimmer et al, in which patients with preexisting anxiety or depression had higher average inpatient postoperative opioid use after EESBS 13 . In the postoperative outpatient setting, patients with anxiety or depression who underwent EESBS required additional opioid prescriptions than those without mental illness 12 . The presence of mood and anxiety disorders have also been predictors of increased postoperative pain across other surgical specialties 20–22 …”
Section: Discussionmentioning
confidence: 80%
“…13 In the postoperative outpatient setting, patients with anxiety or depression who underwent EESBS required additional opioid prescriptions than those without mental illness. 12 The presence of mood and anxiety disorders have also been predictors of increased postoperative pain across other surgical specialties. [20][21][22] Identifying anxiety or depression as a predictor of postoperative pain calls for perioperative mental health optimization, such as the use of preoperative screening, education, and targeted mental health therapy to reduce postoperative opioid use.…”
Section: Preoperative Optimization: Anxiety and Depression Affects Po...mentioning
confidence: 99%
See 1 more Smart Citation